Eco-friendly Management of Garlic Thrips (Thrips tabaci) (Thysanoptera: Thripidae) through different Herbal Pesticides - Ali, Mehran; Ahmad, Adil; Muhammad Mansoor,; Muhammad Abdullah,; Zaib, Shayan; Shahab Uddin,; Muhammad Haroon,; Bibi, Sami; Hussain, Riaz; Amanullah, (Indus Journal of Bioscience Research, 2024)
Garlic (Allium sativum) is the most important vegetable crop in Pakistan. Many insect pests attack the garlic crop, but thrips are the most important one. The experiment was conducted in a local farmer field at District Swat and randomized complete block design was followed with three replications. The plant extracts were used were viz., Tobacco leaves Extract 50%, Neem leaves Extract 50%, and Parthenium leaves Extract 50%, and Chinaberry fruit extract 50% respectively. The lowest means percent infestation (6.53, 2.03) and highest % reduction (87.20, 96.23) after both spray application was recorded in plots treated with chinaberry fruit extract. The plot treated with Neem leaves extract and Tobacco leaves was found least effective with maximum percent infestation (8.27, 4.23) (8.83, 3.93) and minimum reduction (78.07, 88.80) (76.23, 88.60) in thrips population and was found similar to each other. The untreated plot had the highest rate of infestation (26.4). It is concluded from the current study that all the botanical extracts gave a significant result against garlic thrips. But botanical extracts of Chinaberry fruit extract gave best results as compared to other plant extracts.